Un exemple de l’utilisation des méthodes de l’analyse des données dans la démarche scientifique en économie - Leredde, Henri; Outreville, J.-François (L'Actualité économique)

(untitled) (HEC Montréal, 1981)
ABSTRACTThe purpose of this paper is both to report on a new methodology in the field of automatic classification, and to discuss the need of these many techniques which are referred to as factor analysis. The paper is designed to explore one group of procedures and to illustrate with a specific example that such a methodology can lead to an awareness of the problem and to a better understanding and forecasting of economic phenomena.